Theoretical Review Of The Implementation Of State Civil Apparatus Ethics In Digitals-Based Public Services (E-Government) In Indonesia - Mohammad Noor Jihan; Desiderius Priyo Sudibyo; Rino Ardhian Nugroho (Journal Of Social Science (JoSS), 2023)
There are practices of service from the government to the community through public services, but in Indonesia there are still many violations of policy, which is a violation of ethics in carrying out or implementing public services and this is often done by civil servants or state civil servants. In terms of e-government, this must follow public service ethics based on the principle of openness, namely information openness, ease of access, and accountability that can be legally accounted for for the public interest. This study conducted a qualitative literature study. The study shows that the ethical principles contained in government regulations, especially Article 10 of the Government Regulation of the Republic of Indonesia Number 42 of 2004 concerning the Development of Spirit Corps Spirit and the PA Pada Server Service Code of Ethics, serve to ensure the provision of high-quality digital public services at the central and provincial levels.